Exploring the supply side dynamics of agritourism in Tamil Nadu - Sennimalai, Sarath; Rao, Badiya Venkata; Sivakumar, S. D. (Frontiers in Sustainable Tourism, 2025)
IntroductionAgritourism is an emerging sector with the potential to drive rural development, economic diversification, and cultural heritage preservation. In Tamil Nadu, agritourism remains underexplored from a supply-side perspective. This study investigates the motivations, operational challenges, and expectations of farmers engaged in agritourism to understand its sustainable development potential.MethodsA mixed-methods approach, guided by grounded theory, was adopted to examine supply-side dynamics. Data were collected from 20 agritourism farm owners in the Coimbatore district of Tamil Nadu through structured questionnaires using a five-point Likert scale. Qualitative insights were also gathered through in-depth interviews to supplement quantitative findings.ResultsFindings reveal that farmers are primarily motivated by economic sustainability, additional income generation, rural heritage preservation, and farm diversification. However, key barriers include inadequate agritourism licensing, insufficient public awareness, and limited marketing efforts. Farmers also face challenges in accessing institutional support and navigating regulatory frameworks.DiscussionTo promote sustainable agritourism, the study recommends the establishment of a dedicated agritourism development committee, the formulation of specific government guidelines, and the integration of agritourism awareness into school curricula. These measures can enhance visibility, create employment opportunities, and ensure the long-term sustainability of agritourism in Tamil Nadu. This research provides valuable insights for policymakers and stakeholders, aiming to strengthen agritourism as a viable rural enterprise.